Bispecific Antibody PD-L1 x CD3 Boosts the Anti-Tumor Potency of the Expanded Vγ2Vδ2 T Cells - Yang, Rui; Shen, Susu; Gong, Cheng; Wang, Xin; Luo, Fang; Luo, Fengyan; Lei, Yang; Wang, Zili; Xu, Shasha; Ni, Qian; Xue, Yan; Fu, Zhen; et al. (Frontiers in Immunology, 2021)
Vγ2Vδ2 T cell-based immunotherapy has benefited some patients in clinical trials, but the overall efficacy is low for solid tumor patients. In this study, a bispecific antibody against both PD-L1 and CD3 (PD-L1 x CD3), Y111, could efficiently bridge T cells and PD-L1 expressing tumor cells. The Y111 prompted fresh CD8+ T cell-mediated lysis of H358 cells, but spared this effect on the fresh Vδ2+ T cells enriched from the same donors, which suggested that Y111 could bypass the anti-tumor capacity of the fresh Vγ2Vδ2 T cells. As the adoptive transfer of the expanded Vγ2Vδ2 T cells was approved to be safe and well-tolerated in clinical trials, we hypothesized that the combination of the expanded Vγ2Vδ2 T cells with the Y111 would provide an alternative approach of immunotherapy. Y111 induced the activation of the expanded Vγ2Vδ2 T cells in a dose-dependent fashion in the presence of PD-L1 positive tumor cells. Moreover, Y111 increased the cytotoxicity of the expanded Vγ2Vδ2 T cells against various NSCLC-derived tumor cell lines with the releases of granzyme B, IFNγ, and TNFα in vitro. Meanwhile, the adoptive transferred Vγ2Vδ2 T cells together with the Y111 inhibited the growth of the established xenografts in NPG mice. Taken together, our data suggested a clinical potential for the adoptive transferring the Vγ2Vδ2 T cells with the Y111 to treat PD-L1 positive solid tumors.